ANIMA-LIE: Android-Based Learning Media on Animal Life Cycles Materials for Elementary School - Sri Lestari Handayani; Island Dahlia (Universitas Pendidikan Ganesha, 2022)
The learning media used for teachers in online learning during the pandemic are only limited to using pictures, words, sounds, videos, and powerpoints in the form of simple presentations. Thus, the media is not optimal in helping students understand the material and does not increase students' direct experience. It takes the development of online learning media based on android applications to solve these problems. This study aims to develop an android-based learning media